Evaluation of the efficacy of 2% Ocimum sanctum gel in the treatment of experimental periodontitis - Hosadurga, Rajesh Ramesh; Rao, Sudarshan Narayan; Edavanputhalath, Rejeesh; Jose, Jobin; Rompicharla, Narayana Charyulu; Shakil, Moidin; Raju, Shashidhara (International Journal of Pharmaceutical Investigation)
Introduction: One of the options for the treatment of periodontitis is local drug delivery systems (LDD). Tulsi (Ocimum sanctum), a traditional herb, has many uses in medicine. It could be a suitable agent as LDD for the treatment of periodontitis. Aim: The aim was to formulate, evaluate the anti-inflammatory activity; assess duration of the action and the efficacy of 2% tulsi (O. sanctum) gel in the treatment of experimental periodontitis in Wistar Albino rat model. Settings and Design: Thirty six Wistar albino rats were randomly assigned to 3 groups. Periodontitis was induced using ligature model. Group 1-control; Group 2-Plain gel and Group 3-2% tulsi (O. sanctum) gel. Materials and Methods: 2% tulsi (O. sanctum) gel were prepared. The anti-inflammatory activity and duration of action were assessed. Silk ligature 5-0 was used to induce periodontitis. Gingival index (GI) and probing pocket depth were measured. Treatment was done. The rats were sacrificed. Morphometric analysis was done using Stereomicroscope and ImageJ software. Statistical Analysis Used: ANOVA followed by Bonferroni’s test, Wilcoxon’s test for intergroup comparison, Mann-Whitney test for P value computation was used. The observations are mean ± standard deviation and standard error of the mean. P < 0.01 as compared to control was considered as statistically significant. Results: 2% tulsi (O. sanctum) gel showed 33.66% inhibition of edema and peak activity was noted at 24 h. There was statistically significant change in the GI and probing pocket depth. Morphometric analysis did not show any significant difference between groups. No toxic effects were seen on oral administration of 2000 mg/kg of Tulsi extract. Conclusions: 2% tulsi (O. sanctum) gel was effective in the treatment of experimental periodontitis.
Keywords: Anti-inflammatory activity; experimental periodontitis; local drug delivery; morphometric analysis; tulsi gel